ANALISIS KOMPOSISI DAN STRUKTUR VEGETASI TERHADAP UPAYA RESTORASI KAWASAN HUTAN TAMAN NASIONAL GUNUNG GEDE PANGRANGO - Wawan Gunawan; Sambas Basuni; Andry Indrawan; Lilik Budi Prasetyo; Herwasono Soedjito (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2011)
Gunung Gede Pangrango National Park (GGPNP) Forest Area has many ecosystem/forest vegetation type. The research aim was to analysis vegetation structure and composition at GGPNP forest area in many forest vegetation type. Research conducted by through vegetation analysis activity by used squared strip method. The results show that form of horizontal stand structure of Natural Forest stand tend to come near form of J-inversed (negative eksponensial) letter spread and form of horizontal stand structure graph of Mixed Rasamala Forest, Mixed Puspa Forest, Damar Forest, and Pine Forest stand be under horizontal stand structure graph of Natural Forest stand. Natural Forest has species number and species diversity index of higher level type at all levels growth of vegetation if compared to others forest vegetation types. Natural Forest has species evenness index of higher level type only at tree growth level, but rather lower at seedling growth level, sapling growth level, and pole growth level if compared to others forest vegetation types. There were 15 vegetation species found at all of forest vegetation types which have potency as pioneer vegetation in restoration activity of GGPNP forest area. Keywords: Vegetation structure and composition, forest restoration, national park